Artificial Intelligence Applications in Healthcare - Aldali, Musab; Mustafa Salama; Hesham Almssmari (AlQalam Journal of Medical and Applied Sciences, 2024)
Nowadays, the employment of artificial intelligence (AI) technologies in healthcare has provided useful outcomes related to decision-making, early diagnosis of diseases, and optimization of patient care services. AI technologies apply to a variety of data sources. The present paper has discussed the latest developments on Artificial Intelligence healthcare applications, AI technologies, benefits, challenges, and ethical considerations. It also has underlined the role of AI in the improvement of diagnosis, prediction, and personalized treatment. On the basis of the present research, it is claimed that the regulation of AI in healthcare is going to decide the fate of AI-ethics in healthcare for at least the coming decade. The ethical agoras on the regulation of AI-healthcare should instead stamp and remain as the imprint on possible and permissible moral and ethical philosophy of AI in healthcare shaped over the years. في الوقت الحاضر، قدم استخدام تقنيات الذكاء الاصطناعي في الرعاية الصحية نتائج مفيدة تتعلق باتخاذ القرار والتشخيص المبكر للأمراض وتحسين خدمات رعاية المرضى. تنطبق تقنيات الذكاء الاصطناعي على مجموعة متنوعة من مصادر البيانات. ناقشت الورقة الحالية أحدث التطورات في تطبيقات الذكاء الاصطناعي في مجال الرعاية الصحية وتقنيات الذكاء الاصطناعي والفوائد والتحديات والاعتبارات الأخلاقية. كما أكدت على دور الذكاء الاصطناعي في تحسين التشخيص والتنبؤ والعلاج الشخصي. على أساس البحث الحالي، يُزعم أن تنظيم الذكاء الاصطناعي في الرعاية الصحية سيقرر مصير أخلاقيات الذكاء الاصطناعي في الرعاية الصحية على الأقل في العقد القادم. بدلاً من ذلك، يجب أن تترك الأغورا الأخلاقية بشأن تنظيم الرعاية الصحية القائمة على الذكاء الاصطناعي بصمة على الفلسفة الأخلاقية الممكنة والمسموح بها للذكاء الاصطناعي في الرعاية الصحية والتي تشكلت على مر السنين